“Wild” languaging : A practice of embodied language learning when integrating dance in early additional language education - Korpinen, Kaisa (Jyväskylän yliopisto, 2025)
A growing body of research has illustrated that embodied and arts-based approaches can holistically support additional language learning. However, more research on the implementation of such approaches is needed to impact pedagogical practices. This study explores how integrating language and dance can create possibilities for embodied language learning in early additional language education. It is based on a project that combined dance with early Swedish language learning in a Finnish primary school. The analytical focus is on animal-themed language and dance integrated activities held when the participating pupils were in second grade. The study draws theoretically on socio-material approaches to language education, which involves considering languaging an activity that engages the entire human being and relates them to other people, materials, and spaces. The data include video recordings of lessons, lesson plans, and the researcher’s embodied experiences and written reflections. An arts-based and post-qualitative research approach is used to analyse and present languaging events. The results indicate that children were activated in languaging through communicative movement exploration that involved children transforming into or becoming animals. The languaging unfolded in unpredictable or “wild” ways in activities that involved repetition, variation, and sense-making with creative movement and sound. Children’s agency in languaging was performed collectively in relation to bodies and materialities of the space in an embodied and creative activity involving peer collaboration and performing. To conclude, the study proposes “wild” languaging as a practice of embodied language learning through dance, and discusses its pedagogical potential for early additional language education.